(untitled) (Modern education and development, 2025)
The article "The Influence of Religious Texts on the Development of Modern Languages" explores how religious texts have impacted the evolution of languages. It examines the role of religious texts in expanding vocabulary, shaping grammatical systems, and creating new social-conceptual terms. Specifically, the study looks at the influence of texts such as the Bible, the Qur’an, and other sacred writings in developing linguistic structures, terminology, and literary styles that continue to influence modern languages today. The article emphasizes the lasting effects of religious teachings on both the spoken and written forms of contemporary languages.